One-pot assembly of complex giant unilamellar vesicle-based synthetic cells - Göpfrich, Kerstin; Haller, Barbara; Staufer, Oskar; Dreher, Yannik; Mersdorf, Ulrike; Platzman, Ilia; Spatz, Joachim P. (ACS synthetic biology, 2019)
Here, we introduce a one-pot method for the bottom-up assembly of complex single- and multicompartment synthetic cells. Cellular components are enclosed within giant unilamellar vesicles (GUVs), produced at the milliliter scale directly from small unilamellar vesicles (SUVs) or proteoliposomes with only basic laboratory equipment within minutes. Toward this end, we layer an aqueous solution, containing SUVs and all biocomponents, on top of an oil-surfactant mix. Manual shaking induces the spontaneous formation of surfactant-stabilized water-in-oil droplets with a spherical supported lipid bilayer at their periphery. Finally, to release GUV-based synthetic cells from the oil and the surfactant shell into the physiological environment, we add an aqueous buffer and a droplet-destabilizing agent. We prove that the obtained GUVs are unilamellar by reconstituting the pore-forming membrane protein α-hemolysin and assess the membrane quality with cryotransmission electron microscopy (cryoTEM), fluorescence recovery after photobleaching (FRAP), and zeta-potential measurements as well as confocal fluorescence imaging. We further demonstrate that our GUV formation method overcomes key challenges of standard techniques, offering high volumes, a flexible choice of lipid compositions and buffer conditions, straightforward coreconstitution of proteins, and a high encapsulation efficiency of biomolecules and even large cargo including cells. We thereby provide a simple, robust, and broadly applicable strategy to mass-produce complex multicomponent GUVs for high-throughput testing in synthetic biology and biomedicine, which can directly be implemented in laboratories around the world.
Gesehen am 05.03.2020